Spacecraft Manoeuvring in the Vicinity of a near-Circular Orbit. - Baranov, Andrey (Cambridge Scholars Publishing, 2022)
This book sets forth the theory of optimal manoeuvring in the vicinity of a circular orbit, describing the possible types of optimal solutions for the transfer and rendezvous problems in cases of coplanar and non-coplanar orbits. In order to find the manoeuvre parameters of these solutions, the book presents extremely simple analytical and numerical-analytical methods, and shows how they can be applied for the solution of basic manoeuvre problems for real spacecraft. It also details effective methods, used both in Russia and across the globe, for the active space object manoeuvre assessment.